Light sampling behaviour regulates circadian entrainment in mice - Steel, LCE; Tam, SKE; Brown, LA; Foster, RG; Peirson, SN (BioMed Central, 2024)
Background: The natural light environment is far more complex than that experienced by animals under laboratory conditions. As a burrowing species, wild mice are able to self-modulate their light exposure, a concept known as light environment sampling behaviour. By contrast, under laboratory conditions mice have little opportunity to exhibit this behaviour. To address this issue, here we introduce a simple nestbox paradigm to allow mice to self-modulate their light environment. Dark nestboxes fitted with passive infrared sensors were used to monitor locomotor activity, circadian entrainment, decision making and light environment sampling behaviour. Results: Under these conditions, mice significantly reduce their light exposure to an average of just 0.8 h across a 24 h period. In addition, mice show a distinct pattern of light environment sampling behaviour, with peaks at dawn and dusk under a ramped light dark cycle. Furthermore, we show that the timing of light environment sampling behaviour depends upon endogenous circadian rhythms and is abolished in mice lacking a circadian clock, indicating a feedback loop between light, the circadian clock and behaviour. Conclusions: Our results highlight the important role of behaviour in modifying the light signals available for circadian entrainment under natural conditions.